Cognitive and executive functions of top level para-karate athletes with intellectual disability - Van Biesen, D.; Augustovicová, D.; Pineda, R. C.; Nemcek, D.; Burns, J. (Psychology of Sport and Exercise, 2025)
Karate is one of the most popular martial arts. This study investigates the cognitive profiles of top-level Para Karate athletes with intellectual disability (ID), aiming to assess the extent to which cognitive abilities are related to athletic performance. Cognitive and executive functions, including decision-making, processing speed, working memory, cognitive flexibility, and inhibitory control, are critical in high-level sports but are often understudied in athletes with ID. We conducted cognitive assessments and executive function tests on a cohort of elite Para Karate athletes (n = 42) aged 27.0 (±6.5) years competing in two separate classes. The K21 class (n = 21) is the traditional class for athletes diagnosed with ID and the K22 (n = 23) is a class for ID-athletes with a significant additional impairment such as a genetic syndrome (e.g., Down syndrome) or functional limitation (e.g., reduced joint mobility). The MANOVA revealed that K21 Para Karate athletes perform significantly better than K22 athletes in the areas related to cognitive processing speed (i.e., simple reaction time), visuospatial processing (block design) and inductive reasoning (matrix reasoning task) with large effect sizes. No significant differences between the classes were found for the executive function measures working memory and inhibitory control. The kata-performance during competition was judged by a panel of seven referees. K21 athletes performed better than K22 athletes and a significant correlation was apparent between kata-performance and one parameter of executive function (i.e., inhibitory control). These results highlight the relation between cognitive development and martial arts performance and provide insights for future studies related to the development of sport-specific classification for athletes with ID. More sophisticated measures are necessary to assess the key determinants of kata performance.